RESEARCH AND INNOVATION – THE CHANCE OF ROMANIA’S ECONOMIC AND FINANCIAL PROGRESS - ELENA CIUCUR; DUMITRU CIUCUR (Challenges of the Knowledge Society)
This paper aims at highlighting the importance of scientific research and economic innovation for economic and financial progress of Romania in the long term. Stem analysis is the gradual accumulation of organic connection between science and how it is used, in a productive vision deeply understood both in the public and private spaces. Financial and economic progress involves scientific research and innovation as the ideal long-term and daily movement of the economy in the short term. So we should keep in mind that not everything is equally urgent and important, in a correct view of the labor and force of the economic and financial effort.